2020
DOI: 10.1007/s10853-020-05190-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving printability of a thermoresponsive hydrogel biomaterial ink by nanoclay addition

Abstract: As a promising biofabrication technology, extrusion-based bioprinting has gained significant attention in the last decade and major advances have been made in the development of bioinks. However, suitable synthetic and stimuli-responsive bioinks are underrepresented in this context. In this work, we described a hybrid system of nanoclay Laponite XLG and thermoresponsive block copolymer poly(2-methyl-2-oxazoline)-b-poly(2-n-propyl-2-oxazine) (PMeOx-b-PnPrOzi) as a novel biomaterial ink and discussed its critica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 59 publications
4
43
0
Order By: Relevance
“…Poly(MeOx)‐poly(2‐ n‐ propyl‐2‐oxazine) has recently been reported as a thermoreversible gelator for 3D printing. [ 210 ] Laponite clays were used to improve the rheology of these materials to allow the printing of high‐resolution structures with good shape fidelity. The mixing of additives to modify rheology of thermoreversible gelators is underexploited outside of poloxamer 407 and is a promising way of enhancing these systems without the need for additional synthetic steps.…”
Section: Thermoreversible Gelatorsmentioning
confidence: 99%
“…Poly(MeOx)‐poly(2‐ n‐ propyl‐2‐oxazine) has recently been reported as a thermoreversible gelator for 3D printing. [ 210 ] Laponite clays were used to improve the rheology of these materials to allow the printing of high‐resolution structures with good shape fidelity. The mixing of additives to modify rheology of thermoreversible gelators is underexploited outside of poloxamer 407 and is a promising way of enhancing these systems without the need for additional synthetic steps.…”
Section: Thermoreversible Gelatorsmentioning
confidence: 99%
“…Previously, a diblock copolymer comprising a hydrophilic PMeOx block and a thermoresponsive PnPrOzi block (PMeOx-b-PnPrOzi = P0) has been introduced as bioink 32 of which the printability and shape fidelity could be significantly improved by addition of Laponite XLG. 33 However, utilization of the bioink for prolonged studies is hampered by dissolution in long-term cell culture. Therefore, additional chemical crosslinking after printing is necessary, for which we chose the well-known post-polymerization modification approach enabling Diels-Alder chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…This led to a considerable improvement of printability of the hydrogel, as evidenced in reduced strand‐fusion and strongly enhance shape fidelity. [ 84 ] Important to note, it appears that the interaction of clay and pMeOx differs considerably from the interactions of clay and PEG, as very recently studied by Le Coeur et al. [ 85 ] The authors observed an increase of storage modulus with increasing concentration of pMeOx in pMeOx/Laponite hydrogels above certain critical concentration, while in case of PEG/Laponite, the storage modulus values reached a plateau.…”
Section: Self‐assembled Poly(2‐oxazoline)smentioning
confidence: 96%